The EU as a Global Actor: The Signiﬁcance of Changes in the World Order From 2004 to 2024 as Regards EU Actorness - Ana Bojinović Fenko; Julija Brsakoska-Bazerkoska (Studia Europejskie, 2024)
Contrary to the prevalent focus on the EU’s capabilities, this article analyses the implications for the EU’s global actorness stemming from changes in the world order. These changes are elaborated upon according to Hettne’s (2005) three-dimensional analysis of the world order, namely, its structure, mode of governance, and form of legitimisation from 2004 when the CEE countries became EU members, to 20 years into their membership in 2024. The main changes of the world order are identiﬁed as: the evolving multipolar international system; a transition from multilateralism towards plurilateralism; and the sporadic unilateral actions and delegitimisation of liberal world order alongside instances of the major powers’ disregard of international law. The article then elucidates the impact of these changes on EU actorness via illustrative case studies of issues dealt within the UN system and the WTO, namely, international trade, sustainable development, climate change, and international peace and security. Findings show that ﬁrstly, in an evolving multipolar international system, the EU aligns strongly with the US which maintains central power in security issues. Secondly, all case studies prove that the EU remains committed to transparent multilateralism. Thirdly, despite instances of increasing state-level disrespect of international law by the US, Russia, and China, the EU’s resolve and advocacy for international norms remains stable. The EU has managed to leverage its economic and normative capabilities along with its positive presence to exert legitimate leadership in, for example, digital trade agenda, the green transition, and artiﬁcial intelligence, but not in enlargement policy. And yet, the war in Ukraine has prompted the Union to bolster its military capability and upgrade its geopolitical strategy towards its neighbours. The authors conclude that the potential development of the EU’s defensive security capability – provided it is developed complementary to its unique market and normative power – offers an opportunity for the EU to reduce its capabilities/expectations gap and enhance its global actorness.